ON THE FORMATION OF ETHNIC IDENTITY - Yu. V. Muhlynkina (Научный вестник МГТУ ГА, 2016)
The article is devoted to the analysis of essence, the contents, formation and development of ethnic identity of the personality (community). The problem of formation of ethnic identity is considered. Complexity and diversity of this process is shown. The advantage of article is the analysis of a wide range of factors and a determinant of formation of ethnic identity. The author refers to them ethnic socialization in a family and in society in general, influence of historical memory, social and economic, political and spiritual factors of life of society.